Dynamic Response of Lined Circular Tunnel in Linear Viscoelastic Medium Due to Moving Ring load - Dwivedi J.P.; Singh V.P.; Krishna Lal R.; Devi S. (My University, 2025)
A two dimensional elasticity analysis for steady state axisymmetric dynamic response of an arbitrarily thick elastic homogeneous hollow cylinder of infinite length, which is imperfectly bonded to the surrounding viscoelastic soil, subject to an axially moving ring load, is presented. The soil is described with the model of Kelvin-Voigt model, and imperfect boundary condition for circular tunnel is adopted. The problem solution is derived in Laplace transform. Numerical solutions for the displacement, pore pressure and stresses are calculated by analytical inversion of the Laplace transformation with respect to the frequency. © 2017 Elsevier Ltd. All rights reserved.